Summer's call : a Michigan day - Hellewell, Amber Lynn; Powers, Gretchen Ellen (Sleeping Bear, 2022)
A family wakes up to the magic of a Michigan summer, enjoying the forests and the lake's beaches. Includes a nature art activity.
Ages 4-8.
Keywords: Summer -- Michigan -- Juvenile fiction; Families -- Juvenile fiction; Summer -- Fiction; Family life -- Fiction; Michigan -- Juvenile fiction; Michigan -- Fiction